Quantum Teleportation (QT) with Qiskit: An Example - Tiwari, Ram Krishna; Paudyal, Harihar (Saptagandaki Journal, 2025)
Quantum computing (QC) is a developing area that relies on fundamental aspects of quantum physics and the principles of traditional computing. This paves the way for creating systems capable of solving problems that a classical system cannot handle. This work defines logical operation related to quantum circuits using Qiskit in Python and explains the basic theoretical protocols for Quantum Teleportation (QT). As an example, this work demonstrates that QT enables the transmission of a quantum state (QS) across two locations, by using a mutually entangled state.